Monetary Policy Rules for Managing Aid Surges in Africa - Buffie, Edward; Adam, Christopher; O'Connell, Stephen; Pattillo, Catherine (Washington, D.C. : International Monetary Fund, 2007)
Since the turn of the century, aid flows to Africa have increased on average and become more volatile. As a result, policymakers, particularly in post-stabilization countries where inflation has only recently been brought under control, have been increasingly preoccupied with how best to deploy the available instruments of monetary policy without yielding on hard-won inflation gains. We use a stochastic simulation model, in which private sector currency substitution effects play a central role, to examine the properties of alternative monetary and fiscal policy strategies in the face of volatile aid flows. We show that simple monetary rules, specifically an (unsterilized) exchange rate crawl and a 'reserve buffer plus float'-under which the authorities set a time-varying reserve target corresponding to the unspent portion of aid financing and allow the exchange rate to float freely once this reserve target is satisfied-have attractive properties relative to a range of alternative strategies including those involving heavy reliance on bond sterilization or a commitment to a 'pure' exchange rate float.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet